Patient Experience of Obstetric Care During the COVID-19 Pandemic: Preliminary Results From a Recurring National Survey - Dani Bradley MPH, MS; Arianna Blaine SM; Neel Shah MD, MPP, FACOG; Ateev Mehrotra MD, MPH; Rahul Gupta MD, MPH, MBA; Adam Wolfberg MD, MPH (Journal of Patient Experience, 2020)
The experience of pregnant and postpartum patients continues to evolve during the COVID-19 pandemic. Limited clinical data and the unknown nature of the virus’ impact and transmission routes have forced constant changes to traditional care delivery. Dependence on telehealth technology such as telephonic and videoconferencing has surged, and patients’ willingness to visit traditional health care facilities has plummeted. We set out to create an ongoing surveillance system to monitor changes to prenatal and obstetric care and the patient experience during the COVID-19 pandemic.